Quality of human capital and location of superior services: an application for the South and Southeast regions of Brazil (Research, Society and Development, 2022)
Recent studies suggest that regional disparities in the quality of human capital are important in explaining different economic growth performances. However, the literature that analyzes its importance as a locational factor for service companies is still scarce. The objectives of this study are: to develop a multidimensional measure of the quality of human capital; and use it in a spatial econometric model to estimate its effect on the location of service companies. For this, panel data will be used for the 254 microregions of the South and Southeast regions of Brazil. The tertiary sector is disaggregated into traditional and superior (knowledge-intensive) services. The main references of the study are Coffey & Polèse (1988) and Pires et al. (2018). It appears that the quality of human capital is an important locational factor for the location of service companies, both traditional and superior.